Interferometric filter-based planar Doppler velocimetry - Lu, Zenghai (Cranfield University, 2008)
This thesis describes the development of a Mach-Zehnder interferometric filter based planar Doppler velocimetry (MZI-PDV) flow measurement technique. The technique uses an entirely new optical system, an unbalanced MZI incorporating glass blocks for wavefront-matching, to replace the iodine cell currently used in conventional PDV. The free spectral range of the interferometric filter can be selected by adjusting the optical path difference of the MZI. This allows the velocity measurement range, sensitivity and resolution to be varied. This system offers no restricts to the choice of laser wavelength of operation which is not the case with most techniques. Two techniques to process the interference fringe images are presented. The first uses the shift of the fringe pattern to determine the Doppler frequency shift along profiles. The second provides a full-field measurement by normalising the received light intensity at each pixel in the image. With the single camera MZI-PDV scheme, exact alignment of the two output images on the active area of the camera is automatic. This eliminates the pixel-matching problem in conventional two camera PDV systems. The technique allows the measurement of up to three components of the flow velocity across a plane defined by a laser light sheet. The construction of a single velocity component MZI-PDV system that incorporates a phase-locking system designed to stabilise the filter is described. Measurements are made on the velocity field of a rotating disc with maximum velocities of ~±70ms-1 and an axis-symmetric air jet (with a nozzle diameter of 20mm) with an exit velocity of ~85ms-1. Standard deviations in the measured velocities were found to be about 2.9 and 2ms-1 for the two processing methods respectively. The system was then modified to make 3-component velocity measurements using imaging fibre bundles to port multiple views to a single detector head, and the standard deviation of the velocity error is around ±3ms-1 for a maximum velocity of ~±30ms-1 in the field of view. The factors that will affect the quality of the interference fringe image are investigated including polarisation sensitivity of the two beam splitters and flatness of the optical components. The inclination angle and the optical path deviation have little effect on the contrast of the interference fringes since collimated light beams, rather than divergent ones, are used in the interferometer.
Keywords: PDV; Mach-Zehnder interferometer; flow measurement; phase control; coherent fibre bundles